KONSEP WALI HAKIM DALAM PEMBARUAN HUKUM KELUARGA ISLAM DI MALAYSIA DAN INDONESIA - Akhmad Fadly Syahputera; Ferdiyan Ferdiyan (Asy-Syari'ah, 2022)
Abstract: Malaysia and Indonesia have reformed Islamic law by codifying Islamic family law through statutory regulations. However, between the two countries, there are quite striking differences in regulating guardian judges. This research aims to find out the substance and relevance of reforming Islamic marriage law in two countries related to judges' guardians. The study used a qualitative descriptive-analytical method with the application of laws, namely the Islamic Family Law (UUKI) of all states in Malaysia, the Republic of Indonesia Law no. 1 of 1974 concerning Marriage (UUP), and the Compilation of Indonesian Islamic Marriage Law, especially regarding magistrate guardians. The study results show that the guardian of the king or guardian of the judge is officially and legally recognized in UUKI Malaysia and UUP Indonesia. However, Malaysia's UUKI has yet to have any detailed rules regarding technical procedures for the practice of magistrate guardians. In contrast, Indonesia has these rules even though they are in the form of a Regulation of the Minister of Religion (PMA). Regarding magistrate guardians, Malaysia and Indonesia are included in the Intra-Doctrinal Reform group, which tends to still adhere to conventional fiqh law.Abstrak: Malaysia dan Indonesia telah melakukan pembaruan hukum Islam dengan mengkodifikasikan hukum keluarga Islam dalam bentuk perundang-undangan. Namun di antara kedua negara tersebut terdapat perbedaan yang cukup mencolok dalam mengatur wali hakim. Tujuan penelitian ini adalah untuk menemukan substansi dan relevansi pembaruan hukum perkawinan Islam di dua negara terkait wali hakim. Penelitian menggunakan metode kualitatif yang bersifat deskriptif analitis dengan pendekatan perundang-undangan yaitu menelaah Enakmen Undang-undang Keluarga Islam (UUKI) semua negara bagian di Malaysia dan UU RI No. 1 Tahun 1974 tentang Perkawinan danKompilasi Hukum Islam atau UU Perkawinan (UUP) Indonesia khususnya tentang wali hakim. Hasil penelitian ditemukan bahwa wali raja atau wali hakim diakui keberadaannya secara resmi dan sah dalam UUKI Malaysia dan UUP Indonesia. Namun dalam UUKI Malaysia belum ditemukan aturan secara rinci mengenai hal-hal terkait prosedur teknis pengamalan wali hakim, sedangkan Indonesia telah mencantumkan aturan tersebut walau dalam bentuk Peraturan Menteri Agama (PMA). Dalam hal wali hakim, Malaysia dan Indonesia termasuk dalam kelompok Intra-Doctrinal Reform yang cenderung masih berpegang kuat pada hukum fikih konvensional.